A cluster-randomised controlled trial of values-based training to promote autonomously held recovery values in mental health workers. (December 2015) - Williams, Virginia; Deane, Frank; Oades, Lindsay; Crowe, Trevor; Ciarrochi, Joseph; Andresen, Retta
Abstract Background The implementation and use of evidence-based practices is a key priority for recovery-oriented mental health service provision. Training and development programmes for employees continue to be a key method of knowledge and skill development, despite acknowledged difficulties with uptake and maintenance of behaviour change. Self-determination theory suggests that autonomy, or a sense that behaviour is self-generated, is a key motivator to sustained behaviour change, in this case practices in mental health services. This study examined the utility of values-focused staff intervention as a specific, reproducible method of autonomy support. Methods Mental health workers (n = 146) were assigned via cluster randomisation to either a values clarification condition or an active problem-solving control condition. Results Results demonstrated that a structured values clarification exercise was useful in promoting integrated motivation for the changed practice and resulted in increased implementation planning. Conclusions Structured values clarification intervention demonstrates utility as a reproducible means of autonomy support within the workplace. We discuss future directions for the study of autonomous motivation in the field of implementation science. Trial registration ACTRN12613000353796